Atrial Fibrillation in Decompensated Heart Failure: Associated Factors and In-Hospital Outcome - Mendes,Fernanda de Souza Nogueira Sardinha (2014)
Background: Studies on atrial fibrillation (AF) in decompensated heart failure (DHF) are scarce in Brazil. Objectives: To determine AF prevalence, its types and associated factors in patients hospitalized due to DHF; to assess their thromboembolic risk profile and anticoagulation rate; and to assess the impact of AF on in-hospital mortality and hospital length of stay. Methods: Retrospective, observational, cross-sectional study of incident cases including 659 consecutive hospitalizations due to DHF, from 01/01/2006 to 12/31/2011. The thromboembolic risk was assessed by using CHADSVASc score. On univariate analysis, the chi-square, Student t and Mann Whitney tests were used. On multivariate analysis, logistic regression was used. Results: The prevalence of AF was 40%, and the permanent type predominated (73.5%). On multivariate model, AF associated with advanced age (p < 0.0001), non-ischemic etiology (p = 0.02), right ventricular dysfunction (p = 0.03), lower systolic blood pressure (SBP) (p = 0.02), higher ejection fraction (EF) (p < 0.0001) and enlarged left atrium (LA) (p < 0.0001). The median CHADSVASc score was 4, and 90% of the cases had it ≥ 2. The anticoagulation rate was 52.8% on admission and 66.8% on discharge, being lower for higher scores. The group with AF had higher in-hospital mortality (11.0% versus 8.1%, p = 0.21) and longer hospital length of stay (20.5 ± 16 versus 16.3 ± 12, p = 0.001). Conclusions: Atrial fibrillation is frequent in DHF, the most prevalent type being permanent AF. Atrial fibrillation is associated with more advanced age, non-ischemic etiology, right ventricular dysfunction, lower SBP, higher EF and enlarged LA. Despite the high thromboembolic risk profile, anticoagulation is underutilized. The presence of AF is associated with longer hospital length of stay and high mortality.